Contrasting sea ice conditions shape microbial food webs in Hudson Bay (Canadian Arctic) - Loïc Jacquemot; Adrien Vigneron; Jean-Éric Tremblay; Connie Lovejoy (ISME Communications, 2022)
Abstract The transition from ice-covered to open water is a recurring feature of the Arctic and sub-Arctic, but microbial diversity and cascading effects on the microbial food webs is poorly known. Here, we investigated microbial eukaryote, bacterial and archaeal communities in Hudson Bay (sub-Arctic, Canada) under sea-ice cover and open waters conditions. Co-occurrence networks revealed a <3 µm pico‒phytoplankton-based food web under the ice and a >3 µm nano‒microphytoplankton-based food web in the open waters. The ice-edge communities were characteristic of post-bloom conditions with high proportions of the picophytoplankton Micromonas and Bathycoccus. Nano‒ to micro‒phytoplankton and ice associated diatoms were detected throughout the water column, with the sympagic Melosira arctica exclusive to ice-covered central Hudson Bay and Thalassiosira in open northwestern Hudson Bay. Heterotrophic microbial eukaryotes and prokaryotes also differed by ice-state, suggesting a linkage between microbes at depth and surface phytoplankton bloom state. The findings suggest that a longer open water season may favor the establishment of a large phytoplankton-based food web at the subsurface chlorophyll maxima (SCM), increasing carbon export from pelagic diatoms to deeper waters and affect higher trophic levels in the deep Hudson Bay.